Pressure dependent structural changes and predicted electrical polarization in perovskite RMnO3. (13th January 2016) - Wu, T; Chen, H; Gao, P; Yu, T; Chen, Z; Liu, Z; Ahn, K H; Wang, X; Cheong, S-W; Tyson, T A
Abstract: High pressure x-ray diffraction measurements on perovskite R MnO3 ( R = Dy, Ho and Lu) reveal that varying structural changes occur for different R ions. Large lattice changes (orthorhombic strain) occur in DyMnO3 and HoMnO3 while the Jahn–Teller (JT) distortion remains stable. Conversely, in the small R -ion system LuMnO3, Mn–O bond distortions are observed between 4 and 8 GPa with a broad minimum in the JT distortion. High pressure infrared measurements indicate that a phonon near 390 cm −1 corresponding to the complex motion of the Mn and O ions changes anomalously for LuMnO3 . It softens in the 4–8 GPa region, which is consistent with the structural change in Mn–O bonds and then hardens at higher pressures. By contrast, the phonons continuously harden with increasing pressure for DyMnO3 and HoMnO3 . Density functional theory methods show that E -phase LuMnO3 is the most stable phase up to the 10 GPa pressure examined. Simulations indicate that the distinct structural change under pressure in LuMnO3 can possibly be used to optimize the electric polarization by pressure/strain.